Pelatihan Analisis Kuantitatif Regresi Data Panel untuk Calon-calon Peneliti Muda: Webinar Analisis dan Pengolahan Data - Deva Diandra Ramadina; Haryo Bimo Budi Indrasto; Akbar Pratama Kartika (Educate: Journal of Community Service in Education, 2024)
This training activity was held with the aim of improving the data processing and analysis skills of young researchers. The activity was carried out online and attended by 69 participants. The results of the questionnaire distribution to the participants showed that 85% of the participants still experienced problems in the data processing process, where the main problem faced was the lack of understanding of the estimation method and systematics of the data processing process. After the training process was carried out, the participants' understanding increased to 80% and 50% of participants expected a follow-up meeting on the data analysis and processing training agenda.